Development of Arabic Reading Materials Based on Moderation with Artificial Intelligence/Tathwir Mawad al-Qira’ah ‘ala Asas al-Wasathiyah bi Istikhdam al-Dzaka’ al-Ishthina’iy - Hamdy, Mohammad Zainal; Umi Machmudah; Danial Hilmi; Wiwik Prasetiyo Ningsih; Jiddah Hassan Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
Qira’ah learning materials often fail to effectively integrate the values of moderation. Additionally, conventional learning methods sometimes struggle to engage students and promote independent learning. Therefore, there is a need for innovative qira’ah materials that not only focus on Arabic reading skills but also instill the values of moderation. Artificial Intelligence (AI) technology offers a solution through interactive features, automated feedback, and adaptive learning, which can enrich the learning experience and deepen students’ understanding of moderation values in Arabic texts. This article explored the development of qira’ah learning materials based on moderation, supported by AI technology, at STAI Darul Ulum Banyuanyar Pamekasan. This research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques included observation, interviews, questionnaires, documentation, and tests. The qualitative data analysis technique used was classification analysis, while the quantitative analysis applies the gain score formula: d=T2−T1d = T2 - T1d=T2−T1. The findings indicate that qira’ah learning materials based on moderation, supported by AI, can enhance students' understanding of moderation values and boost their learning motivation. With interactive features, learning becomes more adaptive and responsive to students’ needs, allowing them to study more independently and effectively. This research offered a substantial contribution to the advancement of Arabic language education that integrates both technological innovation and the principles of moderation. It highlighted how AI integration in qira’ah materials can significantly improve learning effectiveness, promote learner autonomy, and embed moderation values in a more profound and contextualized way.